√2 +√8=3 (2 ^1/2)
1) Solving this expression we have
![\begin{gathered} \sqrt[]{2}\text{ +}\sqrt[]{8}= \\ \sqrt[]{2}\text{ +2}\sqrt[]{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hwsuxkdcjpl9a9lyqah82zm570xbqbbdmh.png)
2) Since we can rewrite this expression using the exponents like this
![\begin{gathered} 2^{(1)/(2)}+2(2^{(1)/(2)})\cong4.24 \\ 3(2^{(1)/(2)})\cong4.24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x28bhzso4mmyynoanks1nl5jh963wo65m1.png)
and since 2 raised to 1/2 works like a term, we can add. Just like we do to
x + 2x = 3x.
So the answer is √2 +√8=3 (2 ^1/2) =
√